El Excentrico, 1959-02-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 5, 1959 [5 de febrero de 1959]. Ano 9, No. 11. Cover contains a flyer for the Annual United Food Drive, which includes photos of Friday Aguilera, Benny Romero, Lupe Reyes, and Joe Rodriguez. This event took place between February 21st and 22nd. Those who donated one can of food could attend a talent show at the Liberty Theatre on the 21st and a dance at the I.E.S. Hall on the 22nd. The headline reads, "Friday Aguilera, Pres. Benny Romero, Vice-Pres. Lupe Reyes, Sec. Joe Rodriguez, Treas. to head to Annual Food Drive to help needy people."